Electrochemical CO2 Reduction Using Electrons Generated from Photoelectrocatalytic Phenol Oxidation. Issue 18 (7th March 2019) - Guo, Chenyan; He, Peng; Cui, Rongrong; Shen, Qi; Yang, Nianjun; Zhao, Guohua
Abstract: Electrochemical CO2 reduction (ECCO2 R) requires electrons, for example, from oxygen evolution reaction (OER). However, such a multiple‐electron‐involved reaction is complicated and kinetically slow, leading to high overpotential. Herein, OER is replaced with photoelectrocatalytic phenol oxidation reaction (PECPOR) that provides electrons for ECCO2 R. In an integrated cell, ECCO2 R is conducted on the cathode of Cu nanowires and PECPOR is performed on the anode of SnO2 and Sb coated TiO2 nanotubes. Significant improvement of ECCO2 R into CO and hydrocarbons is realized when PECPOR is conducted at a high current density. The use of this integrated system results in the reduction of the specific energy consumption by a factor of 51.33%, compared with the utilization of two half‐cells for individual ECCO2 R and PECPOR. This study thus proposes a novel strategy to couple ECCO2 R with PECPOR and eventually to tackle the problems of environmental pollution and energy crisis. Abstract : The electrons for electrochemical CO2 reduction (ECCO2 R), are often provided by the oxygen evolution reaction (OER). Herein, the OER is replaced by the photoelectrocatalytic phenol oxidation reaction (PECPOR). In an integrated cell, the required electric energy is reduced by a factor of 51.33% compared to that using two half‐cells for individual ECCO2 R and PECPOR. This strategy paves the way for a new approach to tackling both the energy crisis and environmental problems.